Subjects With Diabetes Mellitus Are at Increased Risk for Developing Tuberculosis: A Cohort Study in an Inner-City District of Barcelona (Spain) - Violeta Antonio-Arques; Violeta Antonio-Arques; Josep Franch-Nadal; Josep Franch-Nadal; Josep Franch-Nadal; Antonio Moreno-Martinez; Antonio Moreno-Martinez; Jordi Real; Jordi Real; Àngels Orcau; Àngels Orcau; Didac Mauricio; et al. (Frontiers Media S.A., 2022)
BackgroundTuberculosis is the leading cause of mortality from lung infectious disease worldwide in recent years, and its incidence has re-emerged in large cities in low-incidence countries due to migration and socioeconomic deprivation causes. Diabetes mellitus and tuberculosis are syndemic diseases, with diabetes being considered a risk factor for developing tuberculosis.ObjectiveTo investigate whether diabetic patients were at increased risk of tuberculosis living in an inner-district of a large city of northeastern Spain.MethodsObservational matched retrospective cohort study based on clinical records from the population of the lowest socioeconomic status in Barcelona (Ciutat Vella district). A cohort including patients with type 1 and type 2 diabetes mellitus in 2007 and new cases until 2016 (8004 subjects), matched 1:1 by sex and age with a non-diabetic cohort. Follow-up period was until December 31st 2018. We evaluated the risk of developing tuberculosis in diabetic patients compared to non-diabetic patients during the follow up period. We used time-to-event analysis to estimate the incidence of tuberculosis, and competing risks regression by clusters and conditional Cox regression models to calculate the hazard ratio (HR) and its 95% confidence intervals (CI).ResultsAmong the 16,008 included subjects, the median follow-up was 8.7 years. The mean age was 57.7 years; 61.2% men and 38.8% women in both groups. The incidence of tuberculosis was 69.9 per 100,000 person-years in diabetic patients, and 40.9 per 100,000 person-years in non-diabetic patients (HR = 1.90; CI: 1.18-3.07). After adjustment for the country of origin, chronic kidney disease, number of medical appointments, BMI, alcoholism and smoking, the risk remained higher in diabetic patients (1.66: CI 0.99-2.77). Additionally, subjects from Hindustan or with a history of alcohol abuse also showed a higher risk of developing tuberculosis (HR = 3.51; CI:1.87-6.57, and HR = 2.73; CI:1.22-6.12 respectively).ConclusionPeople with diabetes mellitus were at higher risk of developing tuberculosis in a large cohort recruited in an inner-city district with a high incidence for this outcome, and low socioeconomic conditions and high proportion of migrants. This risk was higher among Hindustan born and alcohol abusers.